Adolescent smoking experimentation as a predictor of daily cigarette smoking. (1st June 2017) - Sargent, James D.; Gabrielli, Joy; Budney, Alan; Soneji, Samir; Wills, Thomas A.
Highlights: The utility of smoking research in youth rests on early predictors of later smoking behavior. Trying smoking in early adolescence identified two-thirds of later daily smokers (sensitivity 66.6%). Trying smoking had a false positive rate of only 7.8% (specificity of 92.2%). All levels of T1 lifetime smoking increased risk of daily smoking 2 years later. Abstract: Objective: The utility of studying substance use during early adolescence depends on how well indicies of lower-level experimentation predict the development of substance use problems. We examined associations between experimental cigarette use at T1, recanting of use 8 months later (T2), and daily smoking at 2 years (T4). Methods: Longitudinal telephone survey of 6522 US youth aged 10–14, examining lifetime cigarette smoking (none, just puffing, 1–19, 20–100, >100) and recanting (i.e., reporting lifetime use at T1, denying ever using at T2) as predictors of T4 daily smoking using multivariable logistic regression. Covariates included sociodemographics, friend/family smoking, school performance, and personality characteristics. Results: The sample was 51% male, 18% Black, 17% Hispanic, with 70% retained at T2. At T1, 407 (8.9%) adolescents reported some smoking, of whom 85 (20.9%) recanted at T2. At T4, 970 reported any smoking, of whom 88 (9.1%) were daily smokers. Any T1 experimentation identified two-thirds of T4 daily smokers (sensitivity = 66.7%) with a false positive rate of 7.8%. T1 lifetime smoking categories were associated with the following adjusted odds ratios for T4 daily smoking (vs. never smokers): 2.7 for recanters (95% confidence interval 0.82, 8.5), 3.5 for few puffs (1.7, 7.0), 9.6 for 1–19 cigarettes (4.1, 22.3), 3.8 for 20–100 cigarettes (1.0, 14.3), and 30.1 for >100 cigarettes (8.1, 111). Conclusions: In this sample experimentation with cigarettes predicted future daily smoking with high utility. The findings provide a rationale for monitoring and reporting any experimentation cigarettes as a tobacco surveillance outcome.